Direct Measurements of Ionic Transport Behavior of Dual-Layer Porous Electrodes. Issue 2 (1st February 2023) - Liu, Baichuan; James, Nicole; Hamedi, Amir-Sina; Yao, Adrian; Trask, Stephen; Mazzeo, Brian; Wheeler, Dean R.
Abstract : To improve power and cycling performance of lithium-ion batteries, dual-layer or porosity-gradient electrodes have been proposed. By engineering a higher porosity close to the separator, the intention is to improve ion transport where it is most impactful. In this research, MacMullin numbers of two dual-layer anode samples are tested using an impedance measurement technique developed previously. To characterize the microstructure of each layer independently, we developed an improved transmission-line model that accounts for each layer's properties.Virtual experiments using COMSOL Multiphysics to simulate impedance measurements are used to examine and improve the accuracy of the numerical inversion procedure. The results for the two dual-layer anodes studied show that MacMullin numbers follow expected trends, though the anodes are quite different from each other.